2017
DOI: 10.7150/ijms.20335
|View full text |Cite
|
Sign up to set email alerts
|

The Extracts of Astragalus membranaceus Inhibit Melanogenesis through the ERK Signaling Pathway

Abstract: Melanin is a normal production protecting skin from environment-causing damage. Plants produce some agents in response to their environment. These agents could be applied in cosmetic production. Some Chinese herbals have immunomodulatory activities and modulate the symptoms of several diseases. Melanogenesis represents a complex group of conditions that are thought to be mediated through a complex network of regulatory processes. Previously, some studies found that the extracts of Astragalus membranaceus (PG2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…One study reported that inhibited MSK1 activation may disrupt the synthesis of melanin [ 30 ]. MAPK pathway modulates the transcription activity of MITF and plays important role in melanin synthesis [ 31 , 32 ]. Extracts of Astragalus membranaceus increased the level of ERK phosphorylation and inhibited the production of melanin in a previous study [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that inhibited MSK1 activation may disrupt the synthesis of melanin [ 30 ]. MAPK pathway modulates the transcription activity of MITF and plays important role in melanin synthesis [ 31 , 32 ]. Extracts of Astragalus membranaceus increased the level of ERK phosphorylation and inhibited the production of melanin in a previous study [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK pathway modulates the transcription activity of MITF and plays important role in melanin synthesis [ 31 , 32 ]. Extracts of Astragalus membranaceus increased the level of ERK phosphorylation and inhibited the production of melanin in a previous study [ 31 ]. Here, reduced expression of MITF was related to inhibiting phosphorylation of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…The bicinchoninic acid (BCA) protein assay (Pierce Biotechnology, Rockford, IL, USA) was used to measure the protein content. Proteins were separated by using SDS-PAGE (8%) and transferred to nitrocellulose membranes 12 . The primary antibodies IDO (Thermo Scientific, Rockford, IL, USA), mTOR (Cell Signaling, Danvers, MA, USA), phosphorylation-mTOR (Cell Signaling), protein kinase B (AKT) (Santa Cruz Biotechnology, Inc. Santa Cruz, CA, USA), phosphorylation-AKT (Santa Cruz Biotechnology, Inc.), p70S6K (Cell Signaling), phosphorylation-p70S6K (Cell Signaling), and β-actin (Sigma Aldrich)) were used to detect the protein expression.…”
Section: Methodsmentioning
confidence: 99%
“…Loliolide and Pj-EE decreased the phosphorylation of CREB protein in the MC1R signaling pathway as well as the expression of MITF and tyrosinase proteins in B16F10 cells ( Figure 3 d and Figure 4 i). Although testing the phosphorylation level of MITF is important to check its involvement in this process [ 40 ], the fact that p-CREB was suppressed by loliolide and Pj-EE led us to consider that controlling expression of MITF by CREB activity ( Figure 3 d and Figure 4 i) is major inhibitory mode of action. This result raised the possibility that loliolide and Pj-EE may modulate the MC1R signaling pathway for the activation of CREB to mediate anti-melanogenic effects.…”
Section: Discussionmentioning
confidence: 99%